(untitled) (UNIZIK Journal of Marketing, 2026)
The study examined the effect of service level agreements (SLASs) on sustainable customer retention in the National Health Insurance Scheme (NHIS), Low retention rate has been the bane of NHIS in Anambra State, undermining its goal of universal healthcare coverage and equitable access. The study adopted descriptive survey design. The data for the study were generated from the Federal Ministries, departments and agencies (MDAs) in Anambra state. From a population of 1296 employees of the said (MDAs), a sample of 249 was determined through the application of a formula developed by Taro Yameni in 1964. An item structured instrument was used to elicit the relevant data after it was validated and tested for reliability. The major statistical tools used were the Pearson inferential statistics of correlation coefficient and multiple regression analysis. Major findings indicate that service performance and response time have significant positive effect on sustainable customer retention in NHIS, Anambra state. The study concludes that NHIS providers can increase customers’ satisfaction, build trust and foster loyalty, ultimately driving sustainable customer retention in Anambra state. The study recommends among others that service providers should prioritize response time so that trust and loyalty may be earned to facilitate sustainable customer retention.